Examining Mental Health Differences between Transfer and Nontransfer University Students Seeking Counseling Services. Issue 2 (2nd April 2016) - Mehr, Kristin E.; Daltry, Rachel
ABSTRACT: This article sought to examine the differences between transfer and nontransfer students on mental health factors, social involvement, and academic success. It was found that transfer students had significantly higher scores on several mental health factors as compared to nontransfer students. It was also found that transfer students were less involved in athletics and campus organizations, but engaged in more work hours per week. Finally, results indicated that the transfer students were not experiencing significant differences in their academic performance compared to nontransfer students. Future research should examine these differences to better understand the impact of the transition and adjustment of transferring to a new institution.